Dynamics of clinical and psychological indicators of patients with anxiety neurotic disorders in the treatment of short-term individual analytical-catarrhal psychotherapy - E. G. Ilchenko; T. A. Karavaeva; Iu. A. Iakovleva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Modern development of psychotherapy involves conceptual integration of methods that allows to increase efciency and provide quality personalized treatment for patients with neurotic disorders, taking into account specifc impact targets. Te article describes the application of short-term individual analyticalcathartic therapy, combining various techniques of dynamic approach. Clinical and individual psychological characteristics of patients with disturbing neurotic disorders in the dynamics reﬂecting the result of the applied therapy were studied. Positive changes in the severity of symptoms, the intensity of psychological defenses, the range of constructive coping mechanisms used, self-esteem and interpersonal relationships are shown. Predictors of successful application of this model of psychotherapy are singled out.